Features of Light Scattering by Surface Fractal Structures - Semchuk, O.Yu.; Vodopianov, D.L.; Kunitska, L.Yu. (Наносистеми, наноматеріали, нанотехнології, 2009)
The average coefficient of light scattering by surface fractal structures is calculated
within the scope of the Kirchhoff’s method. Two-dimensional bandlimited
Weierstrass function is used to simulate a scattering surface. On the
basis of numerical calculations of average scattering coefficient, the scattering
indicatrixes for various surfaces and incidence angles are calculated. The
analysis of the indicatrixes leads to the following conclusions: the scattering is
symmetric about the incidence plane; with the increase of surface calibration
degree, the scattering pattern becomes more complicated; the greatest intensity
of the scattered wave is observed along the mirror direction; there are
other directions, in which the intensity bursts are observed. В рамках Кирхгоффової методи розраховано середній коефіцієнт розсіяння світла поверхневими фрактальними структурами. Для моделювання
розсіювальної поверхні використовувалася двовимірна, обмежена смугою
Вейєрштрассова функція. Виконано чисельні розрахунки середнього коефіцієнта розсіяння та побудовано індикатриси розсіяння для різних типів поверхонь та кутів падіння. Аналіза індикатрис розсіяння призводить
до наступних висновків: розсіяння є симетричним відносно площини падіння; зі збільшенням ступеня калібрування поверхні картина розсіяння
ускладнюється; найбільша інтенсивність розсіяної хвилі спостерігається
в дзеркальному напрямку і, крім того, існують напрямки, в яких спостерігаються сплески інтенсивности. В рамках метода Кирхгофа рассчитан средний коэффициент рассеяния
света поверхностными фрактальными структурами. Для моделирования
рассеивающей поверхности использовалась двумерная, ограниченная полосой функция Вейерштрасса. Произведены численные расчеты среднего
коэффициента рассеяния и построены индикатрисы рассеяния для различных поверхностей и углов падения. Анализ индикатрис рассеяния
приводит к следующим заключениям: рассеяние является симметричным
относительно плоскости падения; с увеличением степени калибровки поверхности картина рассеяния усложняется; наибольшая интенсивностьрассеянной волны наблюдается в зеркальном направлении и, кроме того,
существуют другие направления, в которых наблюдаются всплески интенсивности.